Nutritional strategies and seasonal adaptations: Enhancing dairy cow productivity and calf development - Tosun, Hİ; Ahmadi, F (Journal of the Hellenic Veterinary Medical Society, 2025)
This study assessed the impact of rumen undegradable protein levels in close-up diets on Holstein Friesian cows, examining milk yield, composition, body condition score, colostrum, and calf weight across seasons. Using a design with two replicates per treatment, 173 multiparous Holstein cows were randomly assigned to COND (Control Diet = 4.2% RUP, 14.3% crude protein) or RUPD (Rumen Undegradable Protein Diet = 6.0% RUP, 17.1% crude protein) diets administered 30 days prepartum. Results showed that dry matter intake was influenced by both season and diet, with RUPD-fed cows exhibiting higher dry matter intake, especially in winter. While milk yield showed no significant seasonal difference, increased dietary rumen undegredable protein correlated with higher milk yield. An inverse relationship existed between milk fat percentage and rumen endegredable protein levels. Milk protein content increased with higher dietary protein, particularly in winter. Calf weight was higher in winter, and colostrum fat and urea nitrogen levels varied with the season. Body condition score remained unaffected by calving season or diet crude protein level. In conclusion, adjusting the rumen undegredable protein content in close-up diets has been shown to enhance dry matter intake, milk production, and calf weight in Holstein cows during the close-up period, thereby positively impacting their nutritional status.